Climatesafety. In case of emergency - Public Interest Research Centre, Powys (Powys, 2008)
"The new Climate Safety report presents recent climate science and delivers two important messages. The first is that climate change is accelerating more rapidly and dangerously than had been predicted by most scientists, including the IPCC. The second is that, because political maneuvering has delayed progress for so long, the imperative for extremely urgent action on national as well as global scales is now paramount. The report goes on to discuss climate targets and solutions. As part of the solutions, deforestation must be halted within decade or two at most and serious decarbonization of the energy sector must begin immediately."